The reflective spin : case studies of teachers in higher education transforming action - Chen, Ai-Yen; Van Maanen, John (World Scientific, 1999)
The new millennium brings with it new challenges and possibilities. A globalised world in which education will be the key to cross-national relations necessitates a fundamental understanding of the way education is practised in different cultures across the world. The Reflective Spin is the first book of its kind - about university teachers, about professionals sharing their experiences in improving learning and teaching practices. The writers of the cases generously share their concerns, struggles, knowledge and insights as they examine the values, assumptions, presuppositions and perspectives about learning and teaching in higher education. Readers will benefit from this sharing of a new reflective experience in a multi-layered, multi-faceted and multi-perspective context.